Enhancing Indonesian Learners’ Comprehension of Japanese Adnominal Clauses through Linguistic Awareness - Maarif, Samsul (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study investigates how the application of Japanese linguistic knowledge can enhance Indonesian learners’ understanding of Japanese adnominal clauses with animate head nouns. Previous experiments revealed that learners had difficulty interpreting semantic roles due to differences between Japanese and Indonesian in case particle usage and clause structure. To address this issue, a two-step method was introduced: identifying the adnominal clause and converting the head noun back into a clause to clarify its semantic role. In this experiment, 20 Indonesian learners at the N3 level were divided into two groups: an experimental group, which received explicit instruction on the method, and a control group, which did not. Results from pre- and post-class tests showed that the experimental group significantly improved in interpreting adnominal clauses. A one-tailed paired t-test confirmed that the improvement was statistically significant. These findings suggest that explicit attention to case particles and clause structures—supported by linguistic knowledge—can help learners accurately comprehend complex sentences. Moreover, knowledge of case particles may serve as a self-monitoring tool for understanding Japanese adnominal clauses. This research highlights the importance of integrating linguistic theory into Japanese language education to address specific learner challengesKeywords: Applied linguistics, focus on form, Japanese language education, adnominal clauses, case particles